Types of Language Style Based on Sentence Structure in the US Presidential Debates 2020 - Yogaswara, Andra Yosia; Fitrawati, Fitrawati (English Language and Literature, 2021)
This research aims at examining the types of language style based on sentence structure in the 2020 US presidential candidate debate. The purpose of this research is to find out the types of language style based on sentence structure used by Trump and Biden in the 2020 US presidential candidate debate. The data were analyzed by using Keraf’s theory (2006). The data were the sentences that contained languages style based on sentence structure uttered by Trump and Biden, and the sources of data in this research were the two videos of US presidential candidate debate 2020 and its script. This research used qualitative-descriptive techniques and quantitative calculation because the data will be presented in statistic. The results of the study show that from 12 types of language style based on sentence structure, there were 11 types of language style based on sentence structure used by Trump, meanwhile there were 10 types of language style based on sentence structure used by biden. From a total of 241 data, as many as 105 sentences were uttered by Donald Trump and 146 sentences were uttered by Joe Biden in the two videos of 2020 US presidential candidate debate containing language style based on sentence structure.